Role of Single Dose Intramuscular Betamethazone in Reducing Hospitalization Rates in Acute Asthma - Jayasree P (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Children with asthma are predisposed to exacerbations. This holds irrespective of the type of asthma the reason for exacerbation can be a viral illness, physical activity or exposure to allergens.  Hospitalization of patients with acute attack poses financial and other problems. Subjects and Methods: The participants of the study were children aged 1-12 years with acute attack of asthma coming to OPD/casualty of department of Paediatrics, Mount Zion medical College, Adoor. Results: Among 74 responders, there were 32 patients had mild type asthma (mild persistent and intermittent) (43.2%), 32 had moderate (moderate persistent) type asthma (43.2%) and 10 had severe (severe persistent) type asthma. The corresponding groups among non- responders were mild-8 (30.8%), moderate 11 (42.3%) and sever e 7 (26.9%). Though it seems that percentage of severe asthma is more among non- responders, (26.9 % v/s 13.6%), the two groups are comparable when analysed statistically (standard error of difference between proportions was 9.5 and observed difference 13.3). the other groups were also comparable. Thus the type of asthma did not affect the response. Conclusion: Thus this study emphasizes the role of single dose IM betamethasone in preventing hospitalization rate in patients with moderate attack of asthma if used early.